Modelo matemático para controle de um sistema ativo de suspensão automotiva - Azevedo, Claudio Marcio Medeiros de (Universidade Federal Rural do Semi-Árido, 2013)
With the aid of the mathematical the man uses representations that are able to explain and interpret phenomena in studies, with this, the use of mathematics with language symbolic leads representation of the problem situation in mathematical terms, which in turn, this model can be understood as a set of symbols and relationships that represent a situation, phenomenon, or a real object to be studied. Therefore, this paper presents a mathematical modeling of quarter suspension system of an automobile in order to obtain a transfer function and then put the system in a state space representation. The second part deals with the problems of stabilization in continuous-time linear systems using static output feedback. The second part deals with the problems of stabilization in continuous-time linear systems using static output feedback. The results presented have as their starting point the concept of subspaces (C,A,B)-invariant algebraically characterized by a pair of coupled Sylvester equations, whose solution can be obtained for systems that verify the condition Kimura, in two stages using the algorithm and Lewis Syrmos. In the case of normal systems as studied in this work will be used the technique of the stabilization for two systems satisfying the condition Kimura, will be simulations of this car passing by two external disturbances, and controller gains employees will be obtained by the methods of allocation poles and coupled Sylvester equations, and finishes the work by making a bond regarding the responses of two arrays of feedback gains
Keywords: Modelagem matemática; Suspensão automotiva; Espaço de estados; Equações de Sylvester; Mathematical modeling; Automotive suspension; State space; Sylvester equations; ENGENHARIAS::ENGENHARIA ELETRICA